Disordered semantic activation in disorganized discourse in schizophrenia: a new pragma‐linguistic tool for structure and meaning reconstruction. Issue 3 (25th February 2013) - Hella, Pertti; Niemi, Jussi; Hintikka, Jukka; Otsa, Lidia; Tirkkonen, Jani‐Matti; Koponen, Hannu
Abstract Background Disorganized speech, manifested as derailment, tangentiality, incoherence and loss of goal, occurs commonly in schizophrenia. Studies of language processing have demonstrated that semantic activation in schizophrenia is often disordered and, moreover, the ability to use contextual cues is impaired. Aims To reconstruct the origins and most plausible intended meanings of disorganized discourse sequences in a clinical interview with a patient with thought‐disordered schizophrenia. Methods & Procedures We assessed the so‐called pragmatic felicity of every turn using a novel tool called the Overall Comprehensibility of Turn (OCT) Scale. In addition to felicity analysis, all topics and referents of turns were registered. Three most disorganized discourse sequences from the transcribed interview were chosen for the thematic and semantic analysis, in which we attempted to reconstruct the structure and meaning of those sequences utilizing (1) the notion of discourse model extending up to contextual background knowledge, (2) the (re)occurrence of topical items, together with (3) the knowledge from findings of disordered semantic activation in schizophrenia. Outcomes & Results The linguistic analyses showed that the disrupted sequences were characterized by (1) unexpected, seemingly irrelevant topic intrusion, (2) pragmatically inappropriate chain of topic extensions, and (3) fuzzy reference together with disturbed ordering of propositions. The underlying causes seemed to be, respectively, (1) long‐term semantic activation of topics, which popped out sporadically along the conversation, (2) overreliance on lexical–semantic associations, and (3) the inability to sequence the utterances and link them together using explicit or implicit bridging assumptions necessary to a coherent and cohesive message. All scrutinized passages violated the expectations of the addressee in on‐line conversation. However, the post‐hoc analysis showed that they contained items which were relevant to the global topic. Conclusions & Implications Latent sources, motivations and even meanings, at least to some extent, of seemingly disorganized utterances can become analysable through linguistic analyses. The results suggest that continuity in the treatment is essential, because a practitioner who shares background knowledge with the patient has better opportunities to capture the relevance of the superficially disorganized utterances. Moreover, especially the most disorganized sequences should warrant thorough attention because they can convey, beneath their unexpected or obscure surface structure, items which are psychologically important to the patient. The results of this study should be taken into account in the training of interactional skills of professionals who work with schizophrenia patients.